ANALISIS PENGARUH SUHU RUANGAN TERHADAP KELUHAN MSDS DAN KELELAHAN KERJA PADA PT ETB - Riadi, Eka; Zetli, Sri (LPPM Universitas Putera Batam, 2022)
The work environment is all conditions that exist around the workplace which in this case will have a significant effect on the results of human work. Temperatures that are too high will cause fatigue, and will even increase MSDS complaints for workers, especially work done manually. In this study, the results of room temperature measurements carried out by researchers showed that the room temperature reached 31°C and the deburring operator was given a workload of up to 30 to 50 kg. The purpose of this study was to determine the categories of complaints of temperature and work fatigue and the factors that affect work fatigue of warehouse workers at PT ETB. The method used in this study is the IFRC method, which can be used to measure the level of fatigue. The results of this study are the fatigue category of warehouse workers at PT ETB is in the high fatigue category. The results of the Spearman correlation test show that work fatigue (sig = 0.02), workload (sig = 0.01) has an effect on room temperature. It is hoped that the leadership of PT ETB can add air conditioning and air vents as well as mechanical equipment for lifting